Concept and Current Status of Data Acquisition Technique for GEM Detector–Based SXR Diagnostics. (1st May 2016) - Wojenski, A; Pozniak, K; Kasprowicz, G; Zabolotny, W; Byszuk, A; Zienkiewicz, P; Chernyshova, M; Czarski, T
Abstract: This work refers to the measurement system for soft-X-ray radiation (SXR) diagnostics using gaseous electron multiplier (GEM) detectors. In terms of tokamak plasma parameter control and optimization, it is important to determine the level of SXR generated by plasma. This work describes the whole system including the GEM detector, electronic modules, and data acquisition (DAQ) path. The structure of the DAQ system is presented in terms of hardware, firmware, and software architecture. The currently developed hardware allows sampling of the GEM detector signals with 125-MHz frequency and real-time field-programmable gate array (FPGA) processing. It enables processing of all events generated by the highest possible photon flux for the GEM detector. The developed FPGA firmware registers digitized GEM detector signals with a global trigger up to 625 kHz with all 64 channels sampling simultaneously and stores them in the local memory. Therefore, it makes it possible to obtain the photon energy spectra at high photon flux (10 5 to 10 6 counts · mm −2 · s −1 ) in online acquisition mode. The software block performs a DAQ system start-up configuration and provides the user interface. The first preliminary results of laboratory tests are also presented.